Procedural justice as a reward to the compliant: an ethnography of police–citizen interaction in police custody - Savigar-Shaw, Leanne (Policing and society, 2022)
This paper contributes to the literature on Procedural Justice Theory (PJT) by exploring its capacity to explain the dynamic interactions between police and citizens within the context of police detention. Analysis is based on observation and interviews in police custody suites (i.e. locations where arrested citizens are formally processed and held) within one of the larger metropolitan police forces in the UK. The qualitative thematic analysis highlights how, in order to adequately understand police–detainee interactions, it is critical that PJT properly recognises (a) the importance of context for framing ‘procedurally fair’ encounters, (b) the central role and consequences of categorisation, and (c) the role of power in shaping police–citizen encounters. The paper concludes by exploring the implications of this research for assumptions regarding the causal ordering often assumed in the PJT literature. Specifically, we suggest that procedural justice is more than merely a mechanistic route to achieving compliance but can also be conceptualised as a ‘reward’ by the powerful to those already willing to be subordinated and acquiescent.